Standard of Care in Clinical Research Involving Human Subjects: A Perspective from Developing World (Bangladesh Journal of Bioethics, 2014)
Standard of care is an ordinary, reasonable formal treatment and diagnostic process that a physician should follow for his/her patient with specific disease. Standard of care followed in one country may not suit to other country; the reason may involve economic conditions, certain norms, beliefs, tradition and culture of that society. It may be considered ethical if it does not exploit human rights and poor vulnerable population, once it exploits the human rights it creates ethical dilemmas that need to be sort out to protect vulnerable population and to make the research more ethical. Patients attending medicine department of Bolan Medical Complex (BMC) Quetta, Balochistan, Pakistan were selected randomly interviewed and requested to fill the questionnaire. The ethical issues in clinical research conducted on human population have been perplexing and remains to be the same in clinical research settings. Exploitive use of research participants in resource poor developing countries has intensified the debate on the ethics of international research and led to increasing attention to exploitation of vulnerable study subjects. The issues of conducting research in developing countries will remain and need to be focused and debated where and whenever require. One has to try sincerely to sort out the ethical problems while conducting a research study, he might fail to solve all the issues but the situation may improve by the time if tried sincerely.DOI: http://dx.doi.org/10.3329/bioethics.v5i2.19617 Bangladesh Journal of Bioethics 2014 Vol.5(2):68-72